Serum transaminase levels and dengue shock syndrome in children - Yoga Putra; Bagus Ngurah Putu Arhana; Ida Safitri; Raka Widiana (Indonesian Pediatric Society, 2014)
Background Clinical and biochemical impacts on liverdysfunction, as manifested by an increase in serum transaminaselevels, are common in dengue infection. Howevei; an association ofelevated serum transaminase and dengue shock syndrome (DSS)has n ot been well-established.Objective To assess for an association between serum transaminaselevels and the presence of DSS in children.Methods A nested, case control study was conducted on childrenaged l month to 12 years admitted to Sanglah Hospital whowere diagnosed with dengue infection. Baseline characteristicsand serum transaminase levels were recorded. Patients who wereincluded in the study were observed for the presence of DSS.Those who had DSS were selected as cases, and those who did notdevelop DSS were selected as controls. Data was analyzed usingbivariate and multivariate methods with 95% confidence intervalsand P value <0.05 was considered as statistically significant.Results Ninety-four children were involeved, 4 7 children in thecase group and the other 4 7 were in the control group. Baselinecharacteristics of the subjects were similar between the case andcontrol groups. Serum aspart ate transaminase (AST) level of2:: 128 U/L and alanine transaminase (ALT) of 2: 40 U/L wereassociated with DSS (OR 10; 95%CI 2.3 to 44.4; P=0.002) and(OR 7 .3; 95%CI 1.6 to 32.9; P= 0.009), respectively.Conclusion Elevated AST and ALT levels were associatedwith an increased risk of DSS in children with dengue infection.